On the rate of convergence of maxima for the generalized Maxwell distribution. Issue 5 (3rd September 2017) - Huang, Jianwen; Wang, Jianjun; Luo, Guowang
ABSTRACT: Let{ X n, n ≥ 1 } be a sequence of independent and identically distributed random variables with common distribution F following the generalized Maxwell distribution. In this paper, we obtain the exact uniform convergence rate of the distribution of the maximum to its extreme value distribution.